The Advantages and Disadvantages of Palm Oil Empty Fruit Bunch on Bricks and Mortar - Jen Hua Ling; Yong Tat Lim; Wen Kam Leong; How Teck Sia (Journal of the Civil Engineering Forum, 2022)
Palm oil has a great commercial value in the global vegetable oil market, due to having several beneficial uniqueness such as significant profits and high yields for farmers, as well as effective and efficient land use. As the second-largest producer of palm oil in the world, Malaysia produces an enormous amount of empty fruit bunch (EFB) as biomass waste, whose proper and improper disposal incurs costs and environmental problems, respectively. This EFB fibre is also used to produce bricks and mortar for building construction, due to being a sustainable solution to environmental problems. Therefore, this study aims to analyze the existing literature related to the application of EFB in the civil engineering field. This focused on the properties of the fibre and its effects on bricks and mortar, to gauge the challenges and prospects of EFB products in the local industry. EFB fibre is a porous voluminous cellulose structure, whose properties vary among each other due to diverse origins, species, and biological growth conditions. This is useful in reducing the weight and thermal conductivity of bricks, as well as slightly increasing their tensile and flexural strengths. However, some disadvantages were observed for the EFB bricks, with the workability and compressive strength being lower. The water absorption of this product was also higher than normal bricks. This confirmed that EFB fibre should be minimally used in bricks and mortar. As a natural fibre, concerns are often observed on inconsistent quality, poor fire resistance, and decay risk, which need to be solved before the use of bricks in the construction industry. This study recommends several patterns of improving the strength, quality, and consistency of EFB bricks, such as the alkaline treatment, which roughens the surface area of the product to enhance the fibre- atrix adhesion.